Simulation of the 23 July 2012 extreme space weather event: What if this extremely rare CME was Earth directed?. Issue 12 (5th December 2013) - Ngwira, Chigomezyo M.; Pulkkinen, Antti; Leila Mays, M.; Kuznetsova, Maria M.; Galvin, A. B.; Simunac, Kristin; Baker, Daniel N.; Li, Xinlin; Zheng, Yihua; Glocer, Alex
<x xml:space="preserve">Abstract</x> [1] Extreme space weather events are known to cause adverse impacts on critical modern day technological infrastructure such as high‐voltage electric power transmission grids. On 23 July 2012, NASA's Solar Terrestrial Relations Observatory‐Ahead (STEREO‐A) spacecraft observed in situ an extremely fast coronal mass ejection (CME) that traveled 0.96 astronomical units (∼1 AU) in about 19 h. Here we use the Space Weather Modeling Framework (SWMF) to perform a simulation of this rare CME. We consider STEREO‐A in situ observations to represent the upstream L1 solar wind boundary conditions. The goal of this study is to examine what would have happened if this Rare‐type CME was Earth‐bound. Global SWMF‐generated ground geomagnetic field perturbations are used to compute the simulated induced geoelectric field at specific ground‐based active INTERMAGNET magnetometer sites. Simulation results show that while modeled global SYM‐H index, a high‐resolution equivalent of the Dst index, was comparable to previously observed severe geomagnetic storms such as the Halloween 2003 storm, the 23 July CME would have produced some of the largest geomagnetically induced electric fields, making it very geoeffective. These results have important practical applications for risk management of electrical power grids.